Physical Exercise in Managing Takayasu Arteritis Patients Complicated With Cardiovascular Diseases - Zhou, Yaxin; Feng, Yuan; Zhang, Wei; Li, Hongxia; Zhang, Kui; Wu, Zhenbiao (Frontiers in Cardiovascular Medicine, 2021)
Takayasu arteritis(TA) is a kind of large-vessel vasculitis that mainly affects aorta and its branches, the patients of which are usually women at relatively young age.The chronic inflammation of arteries can lead to stenosis, occlusion, dilatation or aneurysm formation. The TA patients have a high risk to be complicated with cardiac diseases, which was the most common cause of death in TA patients. This review briefly summarizes the main cardiac complications of TA and focuses on the important role of either physical activity or exercise training in the prevention, treatment and rehabilitation for the patients with cardiovascular diseases(CVD) especially the cardiac diseases. In conclusion, rheumatologists need to give an individual exercise prescription for TA patients to maximumly improve the outcomes .